2016
DOI: 10.4322/2359-6643.04110
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade da aplicação de composto de lodo de esgoto no cultivo inicial de eucalipto

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. ABSTRACTThis work evaluated the feasibility of the use of sludge composed from a domestic sewage treatment plant as fertilizer for initial eucalyptus cultivation, urograndis hybrid. The experiment was conducted in a greenhouse, at CCA -UFSCar, Araras, SP, from November 12, 2014 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
0
0
3
Order By: Relevance
“…However, there was no increase in the leaf micronutrient concentrations in relation to the application of CF and the CT. The same behavior was observed by Bertolazi et al [35] and Prates et al [24] in their studies with eucalyptus and soybean crops, respectively. In all cases, soil Zn concentration had a significant increase with increasing CSS rates, which demonstrated that the absorption of micronutrients is related to soil-plant interactions and also governing the competitive/inhibitory processes with other micronutrients [24].…”
Section: Attributessupporting
confidence: 85%
“…However, there was no increase in the leaf micronutrient concentrations in relation to the application of CF and the CT. The same behavior was observed by Bertolazi et al [35] and Prates et al [24] in their studies with eucalyptus and soybean crops, respectively. In all cases, soil Zn concentration had a significant increase with increasing CSS rates, which demonstrated that the absorption of micronutrients is related to soil-plant interactions and also governing the competitive/inhibitory processes with other micronutrients [24].…”
Section: Attributessupporting
confidence: 85%
“…O teor inicial de MO do lodo foi de 29 dag.kg -1 , sendo considerado baixo para os padrões encontrados em outros estudos, por obterem teores médios entre 45,6 e 73,0 dag. kg -1 (BOZKURT et al, 2010;BERTOLAZI et al, 2016;KULIKOWSKA, 2016).…”
Section: Resultsunclassified
“…A disposição do lodo em solos agrícolas é considerada alternativa sustentável para destinação desse resíduo, uma vez que substitui parcialmente a adubação mineral e melhora as condições físicas, químicas e biológicas do solo (BERTOLAZI et al, 2016;GARCIA, 2017). Além disso, o LE atua como condicionador do solo, melhorando a capacidade de troca catiônica, a estrutura do solo e também as atividades da microbiota, as quais, pela respiração, criam um ambiente oxirredutor, sendo, portanto, fundamentais na dinâmica de nutrientes e compostos orgânicos na solução do solo (SANTOS et al, 2011;MONDAL et al, 2015;IGNATOWICZ, 2017).…”
Section: Rodrigues Mn Et Alunclassified
“…Muitos aspectos da utilização do lodo florestal foram investigados no início da década de 1970, como: tecnologia aplicada, práticas de manejo e operacionais e monitoramento de impactos ambientais (Silva et al, 2017). A aplicação de lodo de esgoto tratado, em quantidades ambientalmente aceitáveis, resultava em elevadas taxas de respostas de crescimento, tanto para plantios jovens, como para áreas já estabelecidas (Bertolazi et al, 2016). A resposta do crescimento à aplicação do lodo de esgoto é tipicamente maior e mais duradoura, quando comparada com fertilização mineral Guedes, 2006).…”
Section: Introductionunclassified